The impact of corruption on political instability Libyan case study (Sebha University Conference Proceedings, 2022)
Corruption is one of the phenomena that affect the continuity of societies and lead to disruption of their development plans. Intellectuals embraced the disease and called for fighting it, and corruption is found in most societies, and it has several forms, including bribery and fraud.  Fraud, favoritism and nepotism, and political corruption is considered the most important of them because in its presence it is present in a number of species.    Corruption is not only bad for much, but it can clog the political process and limit the process of reaching harm.  It increases wars, feuds, and political amalgamation, with the absence of citizens in the political system and its institutions,  And it leads to chaos and lack of continuity in society. In the case of Libya, the effect of corruption, and the fact that Lewis was a third anti-terrorist that did not seek to reach the intrusions and calm down, where the moi began  The various political struggles in gaining the loyalty of Al-Mawy by unleashing their hands on corruption in all its forms and types in order to ensure  Its protection and continuity in power, in the money, is a guarantee of his loyalty.  Al-Mawy created a kind of disagreement between the conflicting political groups in order for them to continue to carry out their work.  It reaped material and moral interests, and became a bargaining chip over the process of political continuity, and formed an armed group to impose  It is her will, no one reaches the rule except through her, and he does not continue to perform his duty and perform his duties except when he protects its purpose, and the exchange  Peace over power has become a fantasy, because the groups are the actors who control the state and its resources, and they have become  It controls the assignment of officials, ambassadors, and representatives of the state. Rather, the matter has come to the ministers’ assignment only to submit to it, and no place  For those who govern Libya except with what is provided to it, in order to be protected and to extend a helping hand to him, so that corruption has become a system that does not control the destiny of Libya.  The state, and the culture of society does not fight the corrupt, rather they have a prestigious place in society, although religious scruples forbid  About humiliation and called to fight it